International perspectives on family violence and abuse : a cognitive ecological approach - Malley-Morrison, Kathleen (Lawrence Erlbaum Associates, 2004)
Ask men and women around the world to define and give examples of abuse in families and they give a wide range of responses. What aspects of cultural and historical experience contribute to differences and similarities in the perspectives on family violence held by citizens of different countries? This is one of the questions addressed in this book, in which definitions and examples of abuse from men and women from every continent and a very diverse set of backgrounds are considered. It also provides information on the extent to which family violence is a recognized problem in each country, an.